2011
DOI: 10.1111/j.1463-5224.2011.00947.x
|View full text |Cite
|
Sign up to set email alerts
|

Cataracts are not associated with retinal detachment in the Bichon Frise in the UK – a retrospective study of preoperative findings and outcomes in 40 eyes

Abstract: This study suggests that the Bichon Frise population in the UK does not appear to have a predisposition for retinal detachment in association with cataract formation or following cataract surgery. Prophylactic random transscleral laser retinopexy or transscleral cryopexy cannot therefore be routinely recommended for Bichon Frises with cataracts in the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 10 publications
1
21
1
1
Order By: Relevance
“…Retinal detachment (RD) is one of the various complications of phacoemulsification in dogs that have been reported in the veterinary literature, with reports suggesting that it occurs in 0–55% of patients . Some reports suggest that there are breed predilections to RD, specifically in the Bichon Frise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinal detachment (RD) is one of the various complications of phacoemulsification in dogs that have been reported in the veterinary literature, with reports suggesting that it occurs in 0–55% of patients . Some reports suggest that there are breed predilections to RD, specifically in the Bichon Frise.…”
Section: Introductionmentioning
confidence: 99%
“…Since the publication of Schmidt's work in 2004, many veterinary ophthalmologists have begun recommending prophylactic retinopexy in Bichon Frises prior to phacoemulsification on the basis of the reported 55% RD in this breed. In 2012, however, it was reported that cataracts in Bichon Frises are not associated with RD in the United Kingdom . In that study of the 34 eyes of Bichon Frises that had phacoemulsification performed without PR, none developed RD.…”
Section: Introductionmentioning
confidence: 99%
“…reported an increased risk of retinal detachment following phacoemulsification in the Bichon Frise. These findings, however, are not supported by a recent survey of Bichons in the UK or a large retrospective survey by Sigle et al . In humans, a younger age, high myopia, male sex, and intraoperative complications including posterior capsular tears are associated with a higher risk of pseudophakic retinal detachment .…”
Section: Discussionmentioning
confidence: 68%
“…54,55 Schmidt et al 55 reported an increased risk of retinal detachment following phacoemulsification in the Bichon Frise. These findings, however, are not supported by a recent survey of Bichons in the UK or a large retrospective survey by Sigle et al 3,56 In humans, a younger age, high myopia, male sex, and intraoperative complications including posterior capsular tears are associated with a higher risk of pseudophakic retinal detachment. 57 In this study, the overall incidence of retinal detachment was 40%, being highest in the Shih Tzu (five of eight; 63%), followed by the Boston Terrier (9 of 17; 53%), Bichon Frise (5 of 10; 50%), Jack Russell Terrier (three of eight; 38%), Labrador Retriever (3 of 10; 30%), and Cocker Spaniel (4 of 19; 21%) ( Fig.…”
Section: Discussionmentioning
confidence: 87%
“…In the past decade, there has also been conflicting data regarding the incidence of RD in Bichon Frises following phacoemulsification. Five studies have evaluated the complication of RD of Bichon Frises, with frequency ranging from 0 to 55% . While Bichon Frises were not the focus of this present study, Bichon Frises (without prophylactic retinopexy) were significantly more at risk to develop RD when compared individually to Labrador Retrievers and Schnauzers, but not when compared to Boston Terriers and Shih Tzu.…”
Section: Discussionmentioning
confidence: 93%